Developing Common Law to Expand the Meaning of the Right to a Fair Trial in South Africa: The Accused's Right to Be Heard before the Court Imposes the Sentence. (May 2013) - Mujuzi, Jamil Ddamulira
The South African Constitution, like constitutions of other countries and international law, guarantees the right to a fair trial. Section 35(3) of the South African Constitution gives a non-exhaustive list of the rights that make up the right to a fair trial. The Constitutional Court held that an accused's right to a fair trial includes the right to be heard before the sentence is imposed. Recently, the Supreme Court of Appeal held that if the accused insists on his right to make submissions before the sentence is imposed, the court is obliged to allow him or her to make the submissions. The Constitutional Court also held recently that the right to a fair trial requires the court, if it contemplates increasing the accused's sentence, to give notice to the accused to make submissions on why the sentence should not be increased. Both courts developed common law. The purpose of this paper is to analyse the two judgments.